Treatments used for obsessive-compulsive disorder-An international perspective - Brakoulias, Vlasios; Starcevic, Vladan; Albert, Umberto; Arumugham, Shyam Sundar; Bailey, Brenda E.; Belloch, Amparo; Borda, Tania; Dell'Osso, Liliana; Elias, Jason A.; Falkenstein, Martha J; Ferrao, Ygor A.; Fontenelle, Leonardo F; et al. (Human psychopharmacology, 2019)
Objective The objective of this study was to characterise international trends in the use of psychotropic medication, psychological therapies, and novel therapies used to treat obsessive–compulsive disorder (OCD). Methods Researchers in the field of OCD were invited to contribute summary statistics on the characteristics of their samples. Consistency of summary statistics across countries was evaluated. Results The study surveyed 19 expert centres from 15 countries (Argentina, Australia, Brazil, China, Germany, Greece, India, Italy, Japan, Mexico, Portugal, South Africa, Spain, the United Kingdom, and the United States) providing a total sample of 7,340 participants. Fluoxetine (n = 972; 13.2%) and fluvoxamine (n = 913; 12.4%) were the most commonly used selective serotonin reuptake inhibitor medications. Risperidone (n = 428; 7.3%) and aripiprazole (n = 415; 7.1%) were the most commonly used antipsychotic agents. Neurostimulation techniques such as transcranial magnetic stimulation, deep brain stimulation, gamma knife surgery, and psychosurgery were used in less than 1% of the sample. There was significant variation in the use and accessibility of exposure and response prevention for OCD. Conclusions The variation between countries in treatments used for OCD needs further evaluation. Exposure and response prevention is not used as frequently as guidelines suggest and appears difficult to access in most countries. Updated treatment guidelines are recommended. Author V. B. would like to acknowledge all the staff at the numerous research centres throughout the world and their participants who contributed valuable data to this large data base. V. B. would also like toacknowledge Prof. Naomi Fineberg and the International College of Obsessive‐Compulsive Spectrum Disorders (ICOCS) who supportedthis project by circulating his invitation to participate in the surveyto its members.This study was sponsored by Nepean Medical Research Founda-tion Grant, Pfizer Neuroscience Grant, National Natural Science Foun-dation of China (Grant 81371340), and Spanish MINECO GrantPSI2013‐44733‐R.